Effects of botulinum toxin on the distribution of succinate dehydrogenase and phosphorylase in fast and slow skeletal muscles of the mouse - Duchen, L. W. (1970)
A sublethal quantity of botulinum toxin was injected into the muscles of one leg in mice. The histochemical localization of succinate dehydrogenase (SD) and phosphorylase (P) in soleus and gastrocnemius was studied at intervals of from one week to 15 months after the injection of toxin. In normal mice the fibres of soleus are rich in SD and poor in P, but in the superficial part of gastrocnemius the majority of fibres are rich in P and poor in SD. After the injection of toxin the muscles became paralysed and atrophied for several weeks during which time the fibres of gastrocnemius lost their staining reactivity for P and the fibres of soleus showed a weakening of the SD reaction. With the recovery from the effects of the toxin the muscle fibres increased in size and in P activity. Recovery commenced sooner in soleus than in gastrocnemius and for several weeks soleus fibres showed a stronger reaction for P than normal, but with longer survival the enzyme reactions in soleus became normal. Recovery in gastrocnemius began about six weeks after the injection of toxin. Many muscle fibres in gastrocnemius became much enlarged while others remained atrophied. Many fibres gave a strong histochemical reaction for both enzymes. These abnormalities in gastrocnemius seemed to be permanent.